Differences in outcomes between older community‐dwelling patients with bipolar disorder and schizophrenia with illness onset at young age. Issue 4 (23rd January 2020) - Liao, Po‐Chiao; Chung, Kuo‐Hsuan; Chen, Pao‐Huan; Kuo, Chian‐Jue; Huang, Yu‐Jui; Tsai, Shang‐Ying
Abstract : Aim: Older community‐dwelling patients with severe mental illness (SMI), particularly those with illness onset at young age, constitute a group of survivors with unique long‐term care needs. Using an Asian sample in Taiwan, we attempted to find out the differences in outcomes related to physical health, cognition, and social functioning between older community‐dwelling adults with bipolar disorder and schizophrenia with early age onset. Methods: Community‐dwelling patients aged >50 years with bipolar I disorder or schizophrenia whose illness developed before the age of 40 years were recruited. Clinical data were obtained by reviewing all available medical records and by interviewing the patients and their reliable family members. Medical morbidities, Mini‐Mental State Examination (MMSE), Cumulative Illness Rating Scale for Geriatrics (CIRS‐G), and Global Assessment of Functioning (GAF) scores were compared between the two groups. Results: In total, 113 bipolar patients and 104 schizophrenic ones (mean ages = 59.8 and 59.2 years, respectively) became the final subjects. The rates of cognitive impairment (MMSE score <24) were comparable in bipolar disorder (26.5%) and schizophrenia (24.0%) and the mean MMSE scores did not significantly differ from each other. The concurrence (54.9%) of cardiovascular disease (CVD) in the bipolar group was also similar to 51.0% in the schizophrenic one. In a multiple logistic regression analysis, the bipolar group exhibited significantly higher CIRS‐G total scores (95% confidence interval (CI) for odds ratio (OR) = 1.01–1.27), body mass index (95% CI for OR = 1.02–1.21), and GAF scores (95% CI for OR = 1.04–1.14). Conclusion: Given better social functioning and the same cognitive function in older community‐dwelling patients with bipolar disorder, they may remain at higher risk for obesity and medical morbidity than schizophrenic patients. Treatments targeting cognitive impairment and CVDs across their life span are both necessary to promote the health of community‐dwellers with SMI.